1977
DOI: 10.1515/znc-1977-3-413
|View full text |Cite
|
Sign up to set email alerts
|

Activation of Chromatin-Bound DNA-Dependent RNA Polymerase (E.C. 2.7.7.6.) in Plant Storage Tissue Slices

Abstract: Chromatin, RNA Polymerase, Potato Tuber Tissue, Aging Phenomenon The synthesis of RNA by chromatin-bound RNA polymerase (E.C. 2.7.7.6.) from white potato tubers proceeds at a low rate, which is enhanced after slicing the tissue, however. Concomitantly DNA template availability as measured with saturating amounts of Escherichia coli polymerase is diminished drastically. Nearest neighbor frequency analysis proved that the RNA synthesized on chromatin of intact tubers is different from that synthesized on chromat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

1979
1979
2014
2014

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…The inhibition by EDTA was probably by complexing with the divalent cations. As in many animal as well as plant systems (16), pyrophosphate inhibited the RNA polymerase reaction but inorganic phosphate did not. Ribonuclease inhibited the reaction about 90%, as did actinomycin D, and deoxyribonuclease inhibited by 80%.…”
Section: Resultsmentioning
confidence: 86%
See 1 more Smart Citation
“…The inhibition by EDTA was probably by complexing with the divalent cations. As in many animal as well as plant systems (16), pyrophosphate inhibited the RNA polymerase reaction but inorganic phosphate did not. Ribonuclease inhibited the reaction about 90%, as did actinomycin D, and deoxyribonuclease inhibited by 80%.…”
Section: Resultsmentioning
confidence: 86%
“…Assay of RNA polymerase. The RNA polymerase activity in a final volume of 0.5 ml was measured by the method of Kahl and Wechselberger (16).…”
Section: Methodsmentioning
confidence: 99%
“…DISCUSSION We have reported previously that the rapid wounding-induced polyribosomes formation in potato tuber tissue is dependent on previous transcription, which in turn is activated immediately after slicing (12). Wounding also greatly enhances the activity of chromatin-associated RNA polymerases (15). In addition, treatment of potato tissue slices with GA3 drastically stimulates RNA and protein synthesis generally (16,22,25).…”
Section: Methodsmentioning
confidence: 88%
“…A wounding-induced increase in nucleolar size (13,22) and an enhanced activity of chromatin-bound RNA polymerases (4,15,16) or increase in template availability (4) are all characteristic features of injured tissues.…”
mentioning
confidence: 99%
“…Wounding of white potato tuber tissue, a widely used model system, induces an increase in the activity of both chromatin-bound DNA-dependent RNA polymerase I and II and consequently the synthesis of ribosomal as well as messenger RNAs [10,11,12]. Nearest-neighbour frequency analysis of the RNA from resting and wounded tissues revealed that the quality of the RNA and hence the quality of transcription change after an injury [11].…”
Section: Introductionmentioning
confidence: 99%